Assessment of strike effectiveness against enemy landing groups considering sequential volleys and combat potential reduction in computer simulation - Neizhpapa, Oleksii; Maksymov, Maksym; Toshev, Oleksandr (Technology audit and production reserves, 2025)
The object of research is a naval landing operations and interactions between anti-ship missiles and naval forces in a variety of simulation scenarios. Computer simulation is an essential tool for modeling and evaluating complex processes. Strategy-oriented video games allow model and interact with multi-layered systems in a modern warfare, in a variety of scenarios. This research presents a framework for modeling naval landing operation in a strategic wargame. The model focused on the interactions between attacking player using transport ships for naval landing, fire-support ships, minesweepers, electronic warfare units, and interceptor aircraft, and defending player which using anti-ship missile launchers and naval minefields. A key objective is to identify optimal defensive strategies under resource constraints, calculation possible unit interactions, to estimate possible outcomes, which can help that determine the best tools to prevent or execute successful naval landing operation. The methodology was implemented using stochastic mathematical model to estimate the effectiveness of anti-ship missiles against different types of ships with different defensive setups. The methodology proposes different approaches, for the defending side player, targeting the most vulnerable or most important parts of attacking player convoy to ensure the most effective way to prevent naval landing operation. Experiment results show the importance of dynamic targets prioritization for the defending player, and allows increase the efficiency of the provided resources up to two times compared to the basic targeting algorithm. The given framework allows to improve realism of naval combat simulations in a video game and offers a scalable foundation for game balance adjustments or potential application in tactical training environments.